Detecting surface roughness on SLS parts with various measuring techniques - Launhardt, Martin; Wörz, Andreas; Loderer, Andreas; Laumer, Tobias; Drummer, Dietmar; Hausotte, Tino; Schmidt, Michael (Polymer Testing, 2016)

Determination of the fundamental dimension development in building direction for laser-sintered parts - Launhardt, Martin; Drummer, Dietmar (Journal of Polymer Engineering, 2019)
The additive manufacturing process of the laser sintering of polymers (LS) allows the production of complex parts right from CAD data. However, the manufactured parts often show dimensional inaccuracies. In order to fundamentally determine the influencing parameters on the accuracy of LS parts, a hatching specimen, a layer-specimen and defined part geometries are manufactured and subsequently measured. These, combined with a theoretical observation of the layer wise geometry buildup, are used to determine the fundamental portions of the development of dimensions in building direction (z-direction). The results indicated a defined powder adhesion height at the top and the bottom of a melted layer, along with the dependency of melt depth and the hatch number for small structures. Depending on the nominal heights of an LS part, either an oversize or undersize was detected.
CRIS-Team WoS Importer:2019-02-21

Developing a patient individualized flexible silicone implant using SLS and vacuum die casting - Launhardt, Martin; Ebel, Nina; Kondruweit, Markus; Weyand, Michael; Volk, Tilmann; Drummer, Dietmar (AIP Conference Proceedings, 2019)

Developing a Patient Individualized Flexible Silicone Implant using SLS and Vacuum Die Casting - Launhardt, Martin; Ebel, Nina; Kondruweit, Markus; Weyane, Michael; Volk, Tilmann; Drummer, Dietmar (PROCEEDINGS OF THE EUROPE/AFRICA CONFERENCE DRESDEN 2017 - POLYMER PROCESSING SOCIETY PPS, 2019)
CRIS-Team WoS Importer:2019-05-03

Failure criterion for PA12 SLS additive manufactured parts - Obst, Philip; Launhardt, Martin; Drummer, Dietmar; Osswald, Paul; Osswald, Tim (Additive Manufacturing, 2018)
Keywords: SLS; Failure criterion; PA12; Additive manufacturing

Failure Criterion for SLS Additive Manufactured Parts - Obst, Philip; Launhardt, Martin; Drummer, Dietmar; Osswald, Paul; Osswald, Tim (SPE Proceedings Antec, 2017)

Investigation of the influence of exposure time on the dual-curing reaction of RPU 70 during the DLS process and the resulting mechanical part properties - Obst, Philip; Riedelbauch, Julius; Oehlmann, Paul; Rietzel, Dominik; Launhardt, Martin; Schmölzer, Stefan; Osswald, Tim A.; Witt, Gerd (Additive Manufacturing, 2020)
Photo-differential scanning calorimetry (Photo-DSC), standard DSC and tensile testing are used in order to investigate the influence of different exposure times on the dual-curing reaction and mechanical properties of RPU 70 specimens produced by the additive manufacturing technology Digital Light Synthesis (DLS). A comparison of reaction enthalpies measured with a Photo-DSC of different exposure times followed by thermal curing and DSC experiments with different exposed DLS green products shows that the degree of thermal cross-linking of the two-component resin RPU 70 is determined by the preceding cross-linking reaction during photo-polymerization. A shorter exposure time of UV-light enhances the subsequent thermal cross-linking, while increased exposure reduces the effect of thermal curing in the second process step. Tensile testing results of specimen produced with custom-made print profiles on the DLS Carbon M2 with different exposure times show that mechanical characteristics such as tensile strength and elongation at break are strongly dependent on the degree of UV-cross-linking. The mechanical characteristics of DLS parts produced with the RPU 70 resin system can therefore be adapted to specific requirements and applications using these customized print profiles with different exposure times.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Additive manufacturing; Continuous liquid interface production; Cross-linking; Differential scanning calorimetry; Digital light processing; Digital light synthesis; DSC; Dual-Curing; M2; Photo-DSC; Photo-polymerization; RPU 70; Thermal curing; Two-Step process; Vat polymerization

Rapid-Manufacturing-Process for Elastomeric Components - Launhardt, Martin; Drexler, Maximilian; Drummer, Dietmar (International Journal of Recent Contributions from Engineering, Science & IT, 2015)

Research on the Influence of Geometry and Positioning on Laser Sintered Parts - Launhardt, Martin; Fischer, Christopher; Drummer, Dietmar (Applied Mechanics and Materials, 2015)

Untersuchung zum Vibrationsschweißen von laserstrahlgesinterten Bauteilen - Wolf, Michael; Launhardt, Martin; Drummer, Dietmar (Joining Plastics - Fügen von Kunststoffen, 2018)